A tale of two Octavias: historical empathy and intimate partner 'violence'. - Lawrence, Sarah (Bulletin of the Institute of Classical Studies, 2023)
This paper starts with the contention that the category of 'violence' is culturally constructed and varies according to one's cultural and historical context. This is not intended to excuse contemporary acts that violate our laws and standards, but instead to provide a platform for examining Roman ideas of acceptable and unacceptable force so far as we can access them via texts written by male members of the elite. By examining Nero's treatment of Octavia as it is depicted in Tacitus' Annals , I argue that we can identify Roman social/moral condemnation of (technically legal) violence inflicted on Octavia by Nero. However, comparison with the depiction of the same events in the anonymous Octavia demonstrates how conditional this condemnation could be on the victim's presentation as a moral and social exemplar.